Actualizing Ihsan: The Historical Evolution and Contemporary Adaptation of Sufi Orders - Lalu Bayu Komala Sakti (The Ulama Cadre Education Program of Great Mosques of Istiqlal (PKUMI), 2025)
This research examines the evolution of Sufism as the practical actualization of ihsan (spiritual excellence), tracing its development from an ethical-ascetic orientation to speculative-philosophical dimensions, its institutionalization into global Sufi orders (tariqah), and its contemporary adaptation mechanisms. The central research question is: How did the diverse streams of Sufi thought, rooted in the concept of ihsan, historically evolve and institutionalize, and what strategies enable them to maintain relevance in a globalized, modern world, particularly in Southeast Asia? This study employs a qualitative library research method with a historical-phenomenological framework. Data is synthesized from foundational Islamic texts like the Hadith, classical Sufi works such as Al-Ghazali's Ihya' 'Ulum al-Din, Rumi's Matsnawi, and Ibn 'Atha'illah's Al-Hikam, modern academic books, and recent peer-reviewed journals. The findings indicate that Sufism, far from being a marginal phenomenon, is a central and dynamic dimension of Islam rooted in the tripartite framework of Islam-Iman-Ihsan. It has evolved through distinct historical periods: formative (9th-12th c.), consolidation during major empires (15th-17th c.), and reformist (17th-19th c.). Its enduring vitality lies in the adaptive capacity of the tariqah structure. In the contemporary era, Sufi orders demonstrate remarkable resilience by embracing digital technologies, engaging in inter-religious dialogue, and continuing a tradition of cultural hybridization. This adaptability ensures Sufism's continued relevance as a living tradition for actualizing ihsan in the modern world.